2019
DOI: 10.3346/jkms.2019.34.e97
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Possible Depression and Post-traumatic Stress Disorder among Community Dwelling Adult Refugees and Refugee Applicants in South Korea

Abstract: BackgroundBecause there has been a recent increase in refugee applications in Korea, the mental health of these refugees merits greater study.MethodsWe surveyed 129 refugees (including those in process of refugee application) and 121 migrant workers living in urban communities, using: the Patient Health Questionnaire-9 for depressive symptoms, the Impact Event Scale-Revised for post-traumatic stress disorder (PTSD) symptoms, and the health questionnaires used in 2016 Korean National Health and Nutrition Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Two studies [37,43] found evidence for an association between unemployment and mental disorder, with five [33,34,39,41,47] finding no evidence. In their study with 90 asylum seekers in Israel, Nakash et al [43] found that unemployment was associated with higher rates of depression (OR = 2.1, 95% CI 1.04-5.09).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies [37,43] found evidence for an association between unemployment and mental disorder, with five [33,34,39,41,47] finding no evidence. In their study with 90 asylum seekers in Israel, Nakash et al [43] found that unemployment was associated with higher rates of depression (OR = 2.1, 95% CI 1.04-5.09).…”
Section: Resultsmentioning
confidence: 99%
“…Morgan et al [41] found no evidence of a relationship between 'not being able to find work', a proxy for unemployment, and anxiety (r = 0.21, p = 0.182), depression (r = 0.035, p = 0.826) or PTSD (r = − 0.106, p = 0.504). Eisen [34] found no evidence of an association between unemployment and PTSD (β = − 0.029, p = 0.766) or depression (β = − 0.036; p = 0.712), a pattern repeated for Sohn [47] with depression (OR = 1.19, 95% CI 0.21-6.61) and PTSD (OR = 1.821, 95% CI 0.34-9.91), Kashyap et al [39] for depression (β = − 0.1; p = 0.28) and PTSD (β = − 0.06; p = 0.51), and Boersma [33] for depression (r = − 0.033, p = 3.61) and somatization (r = − 0.04, p = − 0.336). Results Five studies [20,40,42,44,49] reported a score for general post-migration living difficulties derived from some of the factors in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies using general samples, 15 [ 17 , 18 , 20 , 30 , 39 , 47 49 , 54 , 55 , 77 , 79 , 83 , 85 , 88 ] reported on the prevalence of suicide attempts ( Table 3 ). The results are ordered by timeframe for the prevalence estimates and then sub-grouped by population type.…”
Section: Resultsmentioning
confidence: 99%
“…The results were either not signi cant or refugees showed a lower risk of suicide attempts [24]. 25 [25] report 0.8% (n = 129) suicide attempts during the past year compared to 0.2% (n = 1,290) in Korean nationals.…”
mentioning
confidence: 90%